A novel approach for custom three‐dimensional printing of a zirconia root analogue implant by digital light processing. Issue 6 (25th April 2016) - Anssari Moin, David; Hassan, Bassam; Wismeijer, Daniel
Abstract: Objectives: This study aimed to explore the feasibility of fabrication of three‐dimensional (3D)‐printed zirconia root analogue implant (RAI) through digital light processing (DLP) technology. Material and methods: One partially edentulous mandibular human cadaver was scanned with a cone‐beam computed tomography (CBCT) system. The scan volumes and data sets were used to create computer‐aided design (CAD) model of the RAI. A high‐end DLP 3D printing technology was used to fabricate the RAI from the CAD model. Within this approach, solid 3D objects are built using a DLP projector to translate voxel data so it is reproduced in liquid photopolymer dispersed with a commercial ceramic, thereby light polymerizing the resin to solid. Optical scanning technology was used to measure the tooth and 3D‐printed RAI. To validate the accuracy of the printed zirconia RAI, the optical surface model of the original tooth and CAD model were superimposed. Results: The differences between the optical scans of the RAI and original tooth are most noticeable towards the apical foramen, showing a disparity for the RAI with a maximum deviation of 0.86 mm. When setting a maximum threshold of 0.5 mm for the 3D‐printed RAI surface to be deviating from the original tooth model and CAD model, measurements show 1.55% and 4.86% of the surface areas are exceeding the threshold distance, respectively. Conclusion: With the use of currently available technology, it is well feasible to 3D print in zirconia a custom RAI.